Method for preparing multi-scale dendronized spiral polyphenylacetylene supramolecular chiral assembly through photo-crosslinking polymerization reaction

By forming supramolecular chiral assembly at the interface of the aqueous phase through branched helical phenylacetylene copolymer, the morphology and scale are regulated by photocrosslinking polymerization reaction, the stability problem of supramolecular chiral assembly system in the aqueous phase is solved, and the stability of supramolecular chiral assembly system is achieved. Transformation from nanofibers to micron-scale films and improve chiral stability.

CN119119364APending Publication Date: 2024-12-13SHANGHAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310688203.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, supramolecular chiral assembly system based on covalent bonding is difficult to control and fix, especially in the aqueous phase, the assembly of artificially synthesized helical polymers is difficult to achieve, and the bionic purpose cannot be achieved, and the supramolecular chiral assembly structure is easy to be Destroyed by external environment.

Method used

Using branched helical phenylacetylene copolymer, supramolecular chiral assembly is formed at the aqueous phase interface through photocrosslinking polymerization, and hydrophilic branched alkoxy ether and hydrophobic phenylacetylene backbone are combined to combine photoresponsive acrylic acid. Ester groups realize the regulation of the morphology and scale of the assembly.

Benefits of technology

A stable supramolecular chiral assembly was successfully formed at the aqueous phase interface, and the morphology transformation from nanofibers to micron-scale films was achieved through light regulation, and the chiral stability of the assembly was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119364A_ABST
    Figure CN119119364A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a multi-scale dendronized spiral polyphenylacetylene supramolecular chiral assembly through photo-crosslinking polymerization reaction, and relates to the field of intelligent chiral materials.A phenylacetylene main chain is used as a hydrophobic structure, hydrophilic tree-shaped alkoxy ether units and photo-responsive acrylate groups are introduced into side chains, and then a chiral source alanine is combined, so that the multi-scale dendronized spiral polyphenylacetylene supramolecular chiral assembly is prepared. The dendronized spiral polyphenylacetylene copolymer is synthesized, the copolymer has the characteristics of radial amphipathicity and photo-crosslinking polymerization reaction, a supramolecular chiral assembly can be formed at an aqueous solution interface, and the crosslinking degree between polymer chains can be regulated and controlled by controlling the illumination time and the illumination intensity; according to the present invention, the structure of the polymer is optimized, such that the assembly behavior of the polymer is further regulated and controlled, the assembly realizes the conversion from the nanometer fiber to the micrometer scale film, the structure and the conformation stability of the chiral assembly are effectively improved, and the new approach is opened up for the preparation of the stable novel chiral functional material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of intelligent chiral materials, and in particular to a method for preparing a multi-scale dendrite helical polyphenylene vinylene supramolecular chiral assembly by photo-crosslinking polymerization. Background Art

[0002] Chirality is one of the most basic characteristics of nature. From the microscopic spinning electrons, DNA in the human body to the macroscopic atmospheric cyclones and even the entire galaxy, chirality is present. Chiral small molecules can be combined in different ways or forms to form many supramolecular chiral assemblies with characteristic morphologies such as helical structures. The driving force of the supramolecular chiral assembly process is non-covalent weak interaction forces, including hydrogen bonds, hydrophobic forces, metal coordination, electrostatic forces and van der Waals forces. Such supramolecular chiral assemblies are widely present in nature, such as the secondary conformation of proteins, and play a key role in the inheritance, replication and signal transduction processes in living organisms.

[0003] The behavior of supramolecular chiral self-assembly is not only related to the chirality and structure of the assembly unit itself, but also closely related to the intermolecular non-covalent bond interaction. Since non-covalent bonds are easily affected by external environmental stimuli, supramolecular chiral assemblies have the advantages of flexible and changeable structures and easy regulation of supramolecular chirality, but they also have the disadvantages of being destroyed by the external environment after the chiral assembly structure and supramolecular chirality. Introducing covalent bonds into the assembly system based on non-covalent interactions is a solution worthy of attention. For example, the document Angew Chem Int Ed, 2021, 60, 18566-18571 records that the covalently cross-linked chiral film designed and prepared realizes the long-term memory of supramolecular chirality, in which the chirality is stored in the covalently cross-linked network. Under external stimuli, the chirality can still be restored after a short disappearance. However, there are currently few studies on supramolecular chiral assembly systems based on covalent bonding, and how to control and fix supramolecular chirality is still a research difficulty, especially for the assembly of artificially synthesized helical polymers in the aqueous phase, which is difficult to achieve and cannot truly achieve the purpose of biomimetic. Therefore, constructing covalently cross-linked supramolecular chiral assemblies of different scales is of great significance in the field of bionics. Summary of the invention

[0004] In order to solve the problems of the prior art, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a branched spiral phenylacetylene copolymer. Different raw material ratios are used to prepare copolymers with different molecular weights. The copolymer has the characteristics of radial amphiphilicity, and the copolymer can be used to prepare a supramolecular chiral assembly with a photocrosslinking polymerization reaction, and the morphology and scale of the supramolecular chiral assembly can be regulated by light regulation.

[0005] One of the purposes of the present invention is to provide a branched spiral phenylacetylene copolymer PGm Ac n The branched helical phenylacetylene copolymer PG has a characteristic topological structure and a branched alkoxy ether as a hydrophilic unit, alanine as a chiral source, an acrylate unit providing a photocrosslinking site, and a phenylacetylene main chain providing a hydrophobic and rigid structure. m Ac n The structural formula is:

[0006]

[0007] Among them, m:n=6-30:1, and OMe is a methoxy group.

[0008] The second object of the present invention is to provide a method for preparing a supramolecular chiral assembly, which comprises the following steps: m Ac n The copolymer is dissolved in pure water to form a copolymer aqueous solution. Driven by non-covalent interactions such as hydrophilic and hydrophobic interactions, the dendritic helical phenylacetylene copolymer spontaneously aggregates at the interface of the aqueous solution to form a supramolecular chiral assembly.

[0009] Furthermore, the concentration of the copolymer aqueous solution is 0.1-50 mg / mL, and after being uniformly dissolved, it is placed at a temperature not exceeding 25° C. and allowed to stand for at least 24 hours.

[0010] The third purpose of the present invention is to provide a method for preparing a photocrosslinked supramolecular chiral assembly, which specifically comprises the following steps: adding 0 to 1 mg / mL of a photoinitiator to the copolymer aqueous solution to obtain a copolymer aqueous solution containing the photoinitiator, and irradiating the copolymer aqueous solution containing the photoinitiator with ultraviolet light perpendicular to the air / solution interface to obtain the photocrosslinked supramolecular chiral assembly.

[0011] Furthermore, the copolymer aqueous solution containing the photoinitiator is drop-coated on a substrate, and the ultraviolet irradiation is performed through an air / solution interface perpendicular to the droplets on the substrate.

[0012] Furthermore, the parameters of the ultraviolet light are: the light intensity is 8mJ / cm 2 , the illumination distance is 3cm, and the illumination time is 0 to 40min.

[0013] The fourth object of the present invention is to provide a branched spiral phenylacetylene copolymer PG m Ac n The preparation method is specifically as follows:

[0014] Dissolving the dendritic spiral phenylacetylene monomer and the phenylacetylene monomer with an acrylate end group in a first portion of dry tetrahydrofuran, stirring and dissolving to obtain a first solution, subjecting the first solution to freeze-drawing treatment to remove moisture and impurities, and then thawing and restoring to room temperature to obtain a mixed monomer;

[0015] Adding the rhodium chloride dimer of chlorobornadiene and the first portion of triethylamine to the second portion of dry tetrahydrofuran to prepare a second solution, wherein the molar ratio between the first portion of triethylamine and the rhodium chloride dimer is 900:1, and the ratio of the molar number of the first portion of triethylamine to the sum of the molar numbers of the dendrite spiral phenylacetylene monomer and the phenylacetylene monomer with an acrylate end group is 3:1, and under a protective atmosphere, adding the second solution into the mixed monomer, and maintaining the mixture in the protective atmosphere until the reaction is completed, to obtain a filling body;

[0016] The filler is sequentially subjected to column chromatography purification with dichloromethane and spin-dried to obtain a dendritic spiral phenylethylidene copolymer.

[0017] Furthermore, the molar ratio of the dendrite spiral phenylacetylene monomer to the phenylacetylene monomer with an acrylate end group is 6 to 30:1.

[0018] Furthermore, the preparation steps of the dendronized spiral phenylacetylene monomer are:

[0019] At room temperature, dissolving a dendritic alkoxy ether monomer having an amino terminal group in the first portion of dry dichloromethane to obtain a third solution;

[0020] In a protective atmosphere, adding the first portion of N,N-diisopropylethylamine and the first portion of 4-ethynyl pentafluorophenol ester to the third solution, and maintaining the solution in the protective atmosphere until the reaction is complete, to obtain a fourth solution;

[0021] The fourth solution is sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain the dendrite helical phenylacetylene monomer.

[0022] Furthermore, the preparation steps of the phenylacetylene monomer having an acrylate end group are as follows:

[0023] Dissolving 2-(2-(2-aminoethoxy)ethoxy)ethanol in a second portion of dry dichloromethane at room temperature to obtain a fifth solution, and dissolving a second portion of 4-ethynyl pentafluorophenol ester in a third portion of dry dichloromethane at room temperature to obtain a sixth solution;

[0024] Adding a second portion of N,N-diisopropylethylamine to the fifth solution to obtain a seventh solution;

[0025] The seventh solution is placed in a protective atmosphere, and the sixth solution is slowly added dropwise. After the addition is completed, the solution is kept in the protective atmosphere until the reaction is completed, thereby obtaining an eighth solution;

[0026] The eighth solution is sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain an intermediate product;

[0027] dissolving all of the intermediate product in a fourth portion of dry dichloromethane to obtain a ninth solution;

[0028] Under a protective atmosphere, adding a second portion of triethylamine to the ninth solution to obtain a tenth solution;

[0029] Add acryloyl chloride to the fifth portion of dry dichloromethane to obtain an eleventh solution;

[0030] adding the eleventh solution to the tenth solution until the reaction is complete, and then adding methanol to quench the reaction to obtain a twelfth solution;

[0031] The twelfth solution is washed with saturated saline. After washing, the lower organic phase is taken out and subjected to spin drying and column chromatography purification in sequence to obtain the phenylacetylene monomer having an acrylate end group.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] The present invention obtains a novel type of dendritic spiral phenylvinylene copolymer by combining hydrophilic dendritic alkoxy ether units and photoresponsive acrylate groups, wherein the polyphenylvinylene main chain has high rigidity and hydrophobicity, while the dendritic alkoxy ether side groups provide hydrophilicity, thereby giving the polymer a radial amphiphilic property and a photocrosslinking polymerization reaction property;

[0034] The branched spiral phenylacetylene copolymer prepared by the present invention can be subjected to supramolecular chiral assembly at the aqueous phase interface to form a fiber assembly. The degree of photocrosslinking polymerization reaction is regulated by controlling light irradiation, and the morphology of the supramolecular chiral assembly is further regulated. The morphology of the assembly realizes the transformation from nanofiber to micrometer-scale film. Ultraviolet irradiation is performed on a high-concentration copolymer aqueous solution to obtain a micrometer-scale chiral film at the solution interface, and the film has chiral stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The dendritic spiral phenylacetylene copolymer prepared in the embodiment of the present invention is in DMSO-d6 1 HNMR spectra, wherein (a) corresponds to Example 1, (b) corresponds to Example 2, and (c) corresponds to Example 3, and the insets in (a), (b) and (c) correspond to the enlarged spectra of the abscissa chemical shift interval (6.20-6.34);

[0036] Figure 2 AFM images of the assemblies of copolymers with different copolymerization ratios at different solution interfaces in the present invention, wherein (a) corresponds to Test Example 3, (b) corresponds to Test Example 2, (c) corresponds to Test Example 1, (d) corresponds to Test Example 6, (e) corresponds to Test Example 5, and (f) corresponds to Test Example 4;

[0037] Figure 3 AFM images of the copolymers with different copolymerization ratios assembled at the aqueous solution interface under different illumination times in the present invention, wherein (a) to (d) are the corresponding images of the samples in Test Example 9 at illumination times of 0s, 30s, 60s and 90s, respectively; (e) to (h) are the corresponding images of the samples in Test Example 8 at illumination times of 0s, 30s, 60s and 90s, respectively; (i) to (l) are the corresponding images of the samples in Test Example 7 at illumination times of 0s, 30s, 60s and 90s, respectively;

[0038] Figure 4 The Raman spectra (a) of the aqueous solution of the copolymer PG16Ac1 using NaNO3 as the internal standard at the gas-liquid interface and in the solution and the semi-quantitative relationship curve of the copolymer concentration (b) are shown in the figure;

[0039] Figure 5 The photopolymerization reaction tracking NMR image of the copolymer PG16Ac1 aqueous solution interface (a) and the reaction degree of C=C in the film after photoirradiation (b), where Figure 5 The left side of (a) is the spectrum of the chemical shift range (4.80-7.75) on the horizontal axis, and the right side is the enlarged view of the chemical shift range (0.50-8.75) on the horizontal axis;

[0040] Figure 6 AFM images (a) to (d) and SEM photos (e) to (h) of the photopolymerization reaction tracking at different illumination times at the interface of the aqueous solution of the copolymer PG16Ac1 of the present invention;

[0041] Figure 7 AFM images of the copolymer aqueous solution prepared in Example 4 of the present invention after irradiation for 30 seconds and aging the assembly in THF for different times (a, b, c) and aging the assembly without irradiation for different times (e, f), as well as the diameter change curve of the assembly (g), wherein (a) to (c) are images corresponding to the aging time of 0h, 12h and 24h of the assembly when irradiated with light for 30 seconds, respectively, and (e) and (f) correspond to the aging time of 0h and 12h of the assembly without irradiation, respectively;

[0042] Figure 8 g is the g of the copolymer film with different copolymerization ratios in the present invention CD value;

[0043] Fig. 9 The temperature-dependent CD spectra and g of the copolymer films with different copolymerization ratios in the present invention are shown in FIG. CD Value change curve, where (a) corresponds to PG1 30 The variable temperature CD spectrum of (a) Ac1, (b) the variable temperature CD spectrum of PG19Ac1, (c) the variable temperature CD spectrum of PG16Ac1, and (d) the variable temperature CD spectrum of g CD Value change curve. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] For ease of understanding, let us first explain the English terms mentioned below:

[0046] G1-NH2: a dendritic alkoxy ether monomer with an amino terminal group;

[0047] DIEA: N,N-diisopropylethylamine;

[0048] OEG-NH2: 2-(2-(2-aminoethoxy)ethoxy)ethanol;

[0049] TEA: triethylamine;

[0050] [Rh(nbd)Cl]2: norbornadiene rhodium chloride dimer;

[0051] Deuterated DMSO: deuterated dimethyl sulfoxide;

[0052] THF: tetrahydrofuran;

[0053] Copolymer: short for dendritic helical phenylethylidene copolymer;

[0054] Assembly: short for molecular chiral assembly;

[0055] Chemical Shift: Chemical shift;

[0056] Width: width;

[0057] Height: height;

[0058] UV: ultraviolet light, UV time: ultraviolet light exposure time;

[0059] Wavelength: wavelength;

[0060] distance to interface: the distance from the Raman light focusing position to the gas-liquid interface

[0061] Figure 4 The vertical axis "A": the integrated intensity of the Raman peak of copolymer PG16Ac1 and NO3 -1 Ratio of integrated intensities;

[0062] The conversion of C=C: the degree of reaction of carbon-carbon double bonds;

[0063] g CD : CD signal of copolymer film;

[0064] CD: abbreviation of circular dichroism;

[0065] AFM: atomic force microscope;

[0066] Absorbance: absorbance;

[0067] δ: The specific chemical shift of the signal peak on the hydrogen nuclear magnetic resonance spectrum.

[0068] First, a specific embodiment of the preparation method of the branched spiral phenylacetylene copolymer (hereinafter referred to as copolymer) is introduced as follows:

[0069] Embodiment 1:

[0070] The preparation process of the dendrite helical phenylacetylene copolymer PG16Ac1 includes the following steps:

[0071] 377.8 mmol of a dendronized spiral phenylacetylene monomer (G1) and 63.0 mmol of a phenylacetylene monomer with an acrylate end group (Ac) were dissolved in 0.1 mL of dry tetrahydrofuran (THF), and the mixture was stirred to obtain a first solution, and the first solution was freeze-extracted to remove moisture and impurities, and then thawed and restored to room temperature to obtain a mixed monomer;

[0072] Rhodium norbornyl chloride dimer ([Rh(nbd)Cl]2) and triethylamine (TEA) are added to THF to prepare a second solution, wherein the molar ratio between TEA and [Rh(nbd)Cl]2 is 900:1, and the amount of TEA is configured according to the ratio of the molar number of TEA to the sum of the molar numbers of G1 monomer and Ac monomer, that is, the molar ratio TEA: (G1+Ac) = 3:1, and 0.2 mL of the second solution is added to the mixed monomers under a protective atmosphere, and the mixture is kept in a protective atmosphere until the reaction is completed to obtain a filling body;

[0073] The filler was sequentially purified by column chromatography using dichloromethane and subjected to spin drying to obtain a dendritic spiral phenylacetylene copolymer having a copolymerization ratio (referring to the molar ratio between monomer G1 and monomer Ac) of about 6, and was labeled as PG6Ac1.

[0074] Furthermore, the preparation method of the branched spiral phenylacetylene monomer comprises the following steps:

[0075] At room temperature, 10.1 mmol of a dendritic alkoxy ether monomer (G1-NH2) having an amino terminal group was dissolved in 100 mL of dry dichloromethane to obtain a third solution;

[0076] In a protective atmosphere, 40.5 mmol of N,N-diisopropylethylamine (DIEA) and 13.2 mmol of 4-ethynyl pentafluorophenol ester were added to the third solution, and the reaction was maintained in the protective atmosphere until the reaction was complete, to obtain a fourth solution;

[0077] The fourth solution was sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain a colorless transparent oily liquid, which was a dendrite helical phenylacetylene monomer, labeled as G1.

[0078] Among them, the branched spiral phenylacetylene monomer and some of the substances used in its preparation and their structural formulas are shown in Table 1:

[0079] Table 1 Substances and structural formulas

[0080]

[0081] Furthermore, the preparation method of the phenylacetylene monomer having an acrylate end group comprises the following steps:

[0082] At room temperature, 9.6 mmol of 2-(2-(2-aminoethoxy)ethoxy)ethanol (OEG-NH2) was dissolved in 50 mL of dry dichloromethane to obtain a fifth solution, and 10.58 mmol of 4-ethynyl pentafluorophenol ester was dissolved in 100 mL of dry dichloromethane at room temperature to obtain a sixth solution;

[0083] Add 19.2 mmol of DIEA to the fifth solution to obtain a seventh solution;

[0084] The seventh solution is placed in a protective atmosphere, and the sixth solution is slowly added dropwise. After the addition is completed, the solution is kept in the protective atmosphere until the reaction is completed, thereby obtaining an eighth solution;

[0085] The eighth solution is sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain a colorless transparent oily liquid, which is the intermediate product PA-OH;

[0086] Dissolve all of PA-OH in 50 mL of dry dichloromethane to obtain a ninth solution;

[0087] Under a protective atmosphere, 33.04 mmol of TEA was added to the ninth solution to obtain a tenth solution;

[0088] 12.4 mmol of acryloyl chloride was added to dry dichloromethane, and the mixed solution was 5 mL to obtain the eleventh solution;

[0089] The eleventh solution was added to the tenth solution until the reaction was complete, and three drops of methanol were added to quench the reaction to obtain a twelfth solution;

[0090] The twelfth solution was washed with saturated brine for three times. After washing, the lower organic phase was taken out and subjected to spin drying and column chromatography purification in sequence to obtain a white solid product, which was a phenylacetylene monomer with an acrylate end group, marked as: Ac.

[0091] Among them, the phenylacetylene monomer with an acrylate end group and some substances involved in its preparation process and their structural formula are shown in Table 2:

[0092] Table 1 Substances and structural formulas

[0093]

[0094] Furthermore, in this example, the reaction was completely detected by TLC plate.

[0095] Furthermore, in this embodiment, the freeze-pumping treatment uses liquid nitrogen freezing and freeze-pumping under high vacuum. In this embodiment, the freeze-pumping treatment is performed in three times, each time for 15 minutes.

[0096] Furthermore, in this embodiment, the second solution is added into the mixed monomer by injecting the second solution into the mixed monomer using a syringe.

[0097] Furthermore, in this embodiment, the protective atmosphere is a nitrogen atmosphere.

[0098] Embodiment 2:

[0099] The steps are basically the same as those in Example 1, except that in step S1, the molar ratio of monomer G1 and monomer Ac is changed to 9:1, specifically, monomer G1 (377.8 mmol) and monomer Ac (42.0 mmol) are dissolved in dry THF (0.1 mL) to obtain a first solution, and after continuing the subsequent steps, the finally obtained branched spiral phenylethene copolymer has a copolymerization ratio of 9, which is marked as: PG9Ac1.

[0100] Embodiment 3:

[0101] The steps are basically the same as those in Example 1, except that in step S1, the molar ratio of monomer G1 to monomer Ac is changed to 30:1, specifically, monomer G1 (377.8 mmol) and monomer Ac (12.6 mmol) are dissolved in dry THF (0.2 ml 2.46 mmol) to obtain the eleventh solution, and after continuing the subsequent steps, the final obtained branched spiral phenyl acetylene copolymer has a copolymerization ratio of 9 and is marked as: PG 30 Ac1.

[0102] The dendritic spiral phenylacetylene copolymers synthesized in Examples 1 to 3 were prepared in DMSO-d6 1 HNMR spectrum Figure 1 As shown, therefore, the structural formula of the branched spiral phenylacetylene copolymer is expressed as:

[0103]

[0104] Among them, m:n=6-30:1, and OMe is a methoxy group.

[0105] Copolymer PG m Ac n The branched alkoxy ether with characteristic topological structure is used as the hydrophilic moiety, alanine is used as the chiral source, the acrylate moiety provides the photocrosslinking site, and the polyphenylene vinylene main chain provides the hydrophobicity and rigid structure.

[0106] The synthesis principle is:

[0107]

[0108] Among them, m:n=6-30:1, and OMe is a methoxy group.

[0109] It can be seen that by adjusting the ratio of monomer G1 to monomer Ac, the ratio of m and n in the copolymer can be adjusted.

[0110] The following is a method for preparing a supramolecular chiral assembly using the above-mentioned dendronized helical phenylacetylene copolymer, the steps of which are as follows: dissolving the dendronized helical phenylacetylene copolymer in pure water, and driving the copolymer to spontaneously aggregate at the interface of the aqueous solution under the drive of non-covalent interactions such as hydrophilic and hydrophobic interactions to form a supramolecular chiral assembly (referred to as assembly).

[0111] Embodiment 4:

[0112] A 0.1 mg / mL aqueous solution of the copolymer PG16Ac1 was prepared, and after being uniformly dissolved, it was placed at a temperature not exceeding 25°C for at least 24 hours to obtain a light-responsive supramolecular chiral assembly of the dendritic helical polyphenylene vinylene copolymer at the pure water interface, which was marked as PG6Ac1-H2O.

[0113] Embodiment 5:

[0114] The steps are basically the same as those in Example 4, except that the copolymer PG6Ac1 is replaced by the copolymer PG19Ac1 in Example 2, which is labeled as PG9Ac1-H2O.

[0115] Embodiment 6:

[0116] The steps are basically the same as those in Example 4, except that the copolymer PG6Ac1 is replaced by the copolymer PG1 in Example 2. 30 Ac1, labeled: PG 30 Ac1-H2O.

[0117] The following is an introduction to copolymer PG1 m Ac n And each assembly prepared therefrom was tested.

[0118] 1. Aggregation behavior of copolymer PG16Ac1 at the interface of aqueous solution

[0119] Embodiment 7:

[0120] The steps are basically the same as those in Example 4, except that the concentration of the copolymer PG6Ac1 is 50 mg / mL.

[0121] In order to study the aggregation behavior of the copolymer at the interface and inside the aqueous solution, NaNO3 was added as an internal standard in Example 7, and a NaNO3 aqueous solution of PG6Ac1 was prepared, and then a confocal micro-Raman spectrometer was used for detection, specifically:

[0122] Test Example 10:

[0123] A PG6Ac1 NaNO3 aqueous solution was prepared, wherein the concentration of the copolymer PG6Ac1 was 50 mg / mL and the concentration of NaNO3 was 0.5 mmol / L.

[0124] like Figure 4 As shown, by the copolymer PG16Ac1 and NO3 -1 The ratio of the Raman peak integrated area was used to analyze the concentration difference of copolymer PG16Ac1 in aqueous solution and at the gas-liquid interface. The results showed that at the gas-liquid interface, the Raman peak integrated intensity of copolymer PG16Ac1 was The ratio of the integrated intensity A is about 25, and when the focusing position increases to 25 μm from the gas-liquid interface, the intensity ratio A drops sharply to 3, indicating that within 25 μm below the gas-liquid interface, there is a significant concentration gradient of copolymer PG16Ac1. However, as the distance increases, the integrated intensity ratio A remains almost unchanged. This shows that the copolymer PG16Ac1 solution maintains almost the same concentration in the deep layer, indicating that the copolymer PG16Ac1 has a high degree of stacking and assembly behavior at the interface of the aqueous solution to form an assembly.

[0125] 2. Supramolecular chiral assembly of copolymers at the interface of aqueous solution

[0126] Comparative Example 1:

[0127] The steps are basically the same as those in Example 4, except that the solvent is replaced by THF from pure water, labeled as PG6Ac1-THF.

[0128] Comparative Example 2:

[0129] The steps are basically the same as those of Comparative Example 1, except that the copolymer PG16Ac1 is replaced by the copolymer PG19Ac1 in Example 2, which is labeled as PG9Ac1-THF.

[0130] Comparative Example 3:

[0131] The steps are basically the same as those in Comparative Example 1, except that the copolymer PG16Ac1 is replaced by the copolymer PG1 in Example 2. 30 Ac1, labeled: PG 30 Ac1-THF.

[0132] In order to study the assembly behavior of the prepared copolymers at the solution interface, the assemblies of different copolymers at different solution interfaces were tested as follows:

[0133] Test Example 1:

[0134] 10 μL of the copolymer aqueous solution prepared in Example 4 was drop-coated on a mica substrate, and the sample of Test Example 1 was obtained after the solution was completely evaporated at room temperature.

[0135] Test Example 2:

[0136] 10 μL of the copolymer aqueous solution prepared in Example 5 was drop-coated on a mica substrate, and the sample of Test Example 2 was obtained after the solution was completely evaporated at room temperature.

[0137] Test Example 3:

[0138] 10 μL of the copolymer aqueous solution prepared in Example 6 was drop-coated on a mica substrate, and the sample of Test Example 3 was obtained after the solution was completely evaporated at room temperature.

[0139] Test Example 4:

[0140] 10 μL of the copolymer THF solution prepared in Comparative Example 1 was drop-coated on a mica substrate, and a sample of Test Example 4 was obtained after the solution was completely evaporated at room temperature.

[0141] Test Example 5:

[0142] 10 μL of the copolymer THF solution prepared in Comparative Example 2 was drop-coated on a mica substrate, and after the solution was completely evaporated at room temperature, a sample of Test Example 5 was obtained.

[0143] Test Example 6:

[0144] 10 μL of the copolymer THF solution prepared in Comparative Example 3 was drop-coated on a mica substrate, and the sample of Test Example 6 was obtained after the solution was completely evaporated at room temperature.

[0145] The samples prepared in Test Examples 1 to 6 were characterized by AFM to study the assembly behaviors of copolymers with different copolymerization ratios in different solutions. Figure 2 As shown in the figure, it can be seen that the branched helical phenylacetylene copolymer can form an ordered structure similar to a fiber in the solution, among which PG 30 Ac1 forms a densely packed fiber structure at the THF interface, PG9Ac1 forms a spiral fiber assembly formed by winding multiple polymer chains at the THF interface, PG6Ac1 forms a densely packed branched fiber at the THF interface, and PG 30 Ac1 forms a two-dimensional film structure that is flat to a certain extent in water, PG9Ac1 forms a very rigid branched fiber assembly in water, and PG6Ac1 also forms a relatively rigid fiber structure in water. This shows that with the increase of monomer Ac content in water, the morphology of the assembly changes from a film to a branched fiber, and the rigidity is significantly enhanced.

[0146] 3. Photo-crosslinking polymerization of copolymers at the interface of aqueous solution

[0147] In order to study the reaction behavior of copolymer PG6Ac1 after irradiation of the aqueous solution interface, Example 8 was prepared and tested as follows:

[0148] Embodiment 8:

[0149] An aqueous solution of copolymer PG16Ac1 was prepared, wherein the concentration of copolymer PG16Ac1 was 50 mg / mL and the concentration of photoinitiator 2959 was 1 mg / mL. After being uniformly dissolved, the aqueous solution was allowed to stand at a temperature not exceeding 25° C. for at least 24 hours to obtain a mixed solution of Example 8.

[0150] Example 8 was subjected to UV irradiation for 5 min, 10 min, 20 min and 40 min in a direction perpendicular to the solution / air interface to obtain a solid-liquid mixture, which was then centrifuged and weighed, and then freeze-dried. The freeze-dried sample was then dissolved in deuterated DMSO and tested after ultrasound. The results are shown in FIG. Figure 5 As shown in the figure, by integrating and calculating the peak at δ = 5.75 at 20min and 40min of UV irradiation, the reaction degree of carbon-carbon double bonds was 3% at 20min of UV irradiation and 4.3% at 40min of UV irradiation, indicating that the reaction degree of copolymer PG16Ac1 at the aqueous solution interface was low during the photocrosslinking polymerization process. AFM and SEM were used to observe the morphology of the film formed at the interface during the irradiation process. Results are shown in Figure 6 During the illumination process, the copolymer PG16Ac1 continuously undergoes photocrosslinking polymerization reaction at the interface of the aqueous solution to form a large-scale film.

[0151] 4. Photo-crosslinking polymerization to regulate the supramolecular chiral assembly of copolymers at the interface of aqueous solution

[0152] In order to study the effect of light on the assembly behavior of the prepared copolymers at the solution interface, photoinitiators were added to aqueous solutions of different copolymers, and the assemblies at the solution interface were tested as follows:

[0153] Embodiment 9:

[0154] The steps are basically the same as those in Example 4, except that 0.0005 mg / mL of photoinitiator 2959 is also added.

[0155] Embodiment 10:

[0156] The steps are basically the same as those in Example 5, except that 0.0005 mg / mL of photoinitiator 2959 is also added.

[0157] Embodiment 11:

[0158] The steps are basically the same as those in Example 6, except that 0.0005 mg / mL of photoinitiator 2959 is also added.

[0159] Test Example 7:

[0160] 10 μL of the copolymer aqueous solution prepared in Example 9 was drop-coated on a mica substrate, and the droplets on the mica surface were irradiated with ultraviolet light for 0 s, 30 s, 60 s and 90 s respectively. After the solution was completely evaporated at room temperature, the sample of Test Example 7 was obtained.

[0161] Test Example 8:

[0162] 10 μL of the copolymer aqueous solution prepared in Example 10 was drop-coated on a mica substrate, and the droplets on the mica surface were irradiated with ultraviolet light for 0 s, 30 s, 60 s and 90 s respectively. After the solution was completely evaporated at room temperature, the sample of Test Example 8 was obtained.

[0163] Test Example 9:

[0164] 10 μL of the copolymer aqueous solution prepared in Example 11 was drop-coated on a mica substrate, and the droplets on the mica surface were irradiated with ultraviolet light for 0 s, 30 s, 60 s and 90 s respectively. After the solution was completely evaporated at room temperature, the sample of Test Example 9 was obtained.

[0165] The morphology of the droplet surface assembly was observed by AFM for each sample of Test Example 7 to Test Example 9. Figure 3 As shown, it can be seen that PG 30 Ac1 formed a thin film assembly on the droplet interface when not irradiated, and a fiber-like structure formed by the curled film could be observed. After 30 seconds of ultraviolet irradiation, a fractal fiber assembly with a diameter of about 25 nm was obtained, and no assembly with a thin film structure was found. With the extension of the irradiation time, the morphology of the fractal fiber assembly became more uniform, the diameter did not change significantly, and the stacking became more compact. The twisted morphology of the assembly could be clearly observed in the AFM images after 60 seconds and 90 seconds of irradiation, among which fewer fiber assemblies had obvious Mhelix structures. PG9Ac1 formed a very rigid fractal fiber assembly on the interface when not irradiated. The diameter is uniform. With the increase of illumination time, the fiber assembly is more densely packed, and a film-like structure is observed in the AFM image of 90s illumination. PG6Ac1 also forms an ordered fractal fiber assembly on the interface. After 30s of illumination, a large number of densely packed fiber assemblies and a small number of film assemblies are observed. After 60s of illumination, a fiber assembly with a larger diameter appears. This may be due to the assembly forming a large-sized film structure through photocrosslinking reaction, which is then curled during the evaporation of the solvent. After 90s of illumination, a very dense film assembly is observed, and no fiber structure appears. By comparing the morphology of the assembly under different illumination times, it can be concluded that photocrosslinking occurs between polymer chains and between assemblies, and finally an assembly with a film morphology is formed.

[0166] 5. Stability of Photocrosslinked Chiral Assemblies

[0167] In order to study the stability of the cross-linked polymer chiral assembly, an aging test was carried out as follows:

[0168] Test Example 12:

[0169] 10 μL of the copolymer aqueous solution prepared in Example 4 was drop-coated on a mica substrate, and the mica substrate was aged in a THF vapor atmosphere for 12 h.

[0170] Test Example 13:

[0171] 10 μL of the copolymer aqueous solution prepared in Example 4 was drop-coated on a mica substrate, the droplets on the mica substrate were irradiated with ultraviolet light for 30 seconds, and then the mica substrate was aged in a THF vapor atmosphere for 12 hours and 24 hours.

[0172] like Figure 7 As shown in the figure, the assembly after irradiation changes from an aggregated state to a dispersed state after aging, but the morphology of the branched fiber assembly can still be observed, and the diameter and height before and after aging remain basically unchanged. The assembly without irradiation has a structural destruction phenomenon after aging, and it is difficult to find any orderly assembly structure. The results show that the photo-crosslinking polymerization reaction effectively solidifies the morphology of the assembly and improves the stability of the assembly.

[0173] VI. Chiral stability of photo-crosslinked chiral films

[0174] Embodiment 12:

[0175] The steps are basically the same as those in Example 7, except that the copolymer PG6Ac1 is replaced by the copolymer PG19Ac1 in Example 2.

[0176] Embodiment 13:

[0177] The steps are basically the same as those in Example 7, except that the copolymer PG6Ac1 is replaced by the copolymer PG1 in Example 3. 30 Ac1.

[0178] 10 μL of each of the copolymer aqueous solutions prepared in Examples 7 to 13 was dripped onto a mica substrate, and the mica surface droplets were exposed to ultraviolet light for 2 minutes. After the solution was completely evaporated at room temperature, a chiral normalization test was performed. CD =(θ / 32980) / Abs to calculate the CD signals (also called chiral signals) of copolymer films with different monomer ratios, where Abs represents the absorbance of the extreme wavelength of the main chain CD signal and θ represents the ellipticity. Figure 8 As shown, PG1 30 The chiral signal of Ac1 copolymer film is the strongest. With the increase of Ac copolymer units in the copolymer, the chirality of the prepared film gradually decreases. The results show that this may be because the former has more chiral units G1, which makes the polymer have a higher helicity.

[0179] 10 μL of each of the copolymer aqueous solutions prepared in Examples 7 to 13 was dripped onto a mica substrate, and the mica surface droplets were exposed to UV light for 2 min. After the solution was completely evaporated at room temperature, the chiral stability of polymer films with different copolymerization ratios was investigated using a variable temperature CD test. Fig. 9 As shown in the figure, the CD signal of the copolymer film decreases significantly at 40°C and continues to decrease with the increase of temperature. The CD signal of the PG16Ac1 and PG19Ac1 copolymer films decreases less with the increase of temperature and at a smaller speed. When the temperature returns to 20°C, the chirality of the two copolymer films can be completely restored to the initial value, while the chirality of the PG1 30 The CD signal of Ac1 copolymer film can only recover to the intensity at 60℃.

[0180] It can be seen that with the increase of the content of Ac copolymer units in the copolymer, the chiral stability of the prepared film becomes better, among which the chiral stability of the PG16Ac1 copolymer film is the strongest and can completely restore the chirality after the temperature returns to room temperature. This shows that under the same lighting conditions, the copolymer film with a higher Ac content has better chiral stability. This may be because the increase in the content of Ac copolymer units helps the film have a higher degree of cross-linking.

[0181] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is limited by the attached embodiments and their equivalents.

Claims

1. A dendrite helical phenylethene copolymer, characterized in that: The branched alkoxy ether with a characteristic topological structure is used as a hydrophilic unit, alanine is used as a chiral source, the acrylate unit provides a photocrosslinking site, and the phenylacetylene main chain provides hydrophobicity and a rigid structure. The structural formula of the branched spiral phenylacetylene copolymer is: Among them, m:n=6-30:1, and OMe is a methoxy group.

2. A method for preparing a supramolecular chiral assembly using the dendritic spiral phenylacetylene copolymer according to claim 1, characterized in that: The dendritic spiral phenylacetylene copolymer is dissolved in pure water to form a copolymer aqueous solution. Driven by non-covalent interaction forces such as hydrophilic and hydrophobic interactions, the dendritic spiral phenylacetylene copolymer spontaneously aggregates at the interface of the aqueous solution to form a supramolecular chiral assembly.

3. The method for preparing a supramolecular chiral assembly according to claim 2, characterized in that: The concentration of the copolymer aqueous solution is 0.1-50 mg / mL. After being uniformly dissolved, the aqueous solution is placed at a temperature not exceeding 25° C. and allowed to stand for at least 24 hours.

4. The method for preparing a photo-crosslinked supramolecular chiral assembly using the dendritic spiral phenylacetylene copolymer according to claim 1, characterized in that: The dendritic spiral phenylvinylene copolymer and a photoinitiator are dissolved in water to form a copolymer aqueous solution containing the photoinitiator, and ultraviolet light is applied perpendicularly to the air / solution interface of the copolymer aqueous solution containing the photoinitiator to obtain a photo-crosslinked polymerized supramolecular chiral assembly, wherein the concentration of the dendritic spiral phenylvinylene copolymer in the copolymer aqueous solution containing the photoinitiator is 0.1-50 mg / mL, and the concentration of the photoinitiator is 0-1 mg / mL.

5. The method for preparing a photo-crosslinked polymerized supramolecular chiral assembly according to claim 4, characterized in that: The copolymer aqueous solution containing the photoinitiator is drop-coated on a substrate, and the ultraviolet irradiation is performed through an air / solution interface perpendicular to the droplets on the substrate.

6. The method for preparing a photo-crosslinked polymerized supramolecular chiral assembly according to claim 4, characterized in that: The parameters of the ultraviolet light are: the light intensity is 8mJ / cm 2 , the illumination distance is 3cm, and the illumination time is 0 to 40min.

7. A method for preparing a dendrite spiral phenylacetylene copolymer, characterized in that: The following steps are involved: Dissolving the dendritic spiral phenylacetylene monomer and the phenylacetylene monomer with an acrylate end group in a first portion of dry tetrahydrofuran, stirring and dissolving to obtain a first solution, subjecting the first solution to freeze-drawing treatment to remove moisture and impurities, and then thawing and restoring to room temperature to obtain a mixed monomer; Adding the rhodium chloride dimer of chlorobornadiene and the first portion of triethylamine to the second portion of dry tetrahydrofuran to prepare a second solution, wherein the molar ratio between the first portion of triethylamine and the rhodium chloride dimer is 900:1, and the ratio of the molar number of the first portion of triethylamine to the sum of the molar numbers of the dendrite spiral phenylacetylene monomer and the phenylacetylene monomer with an acrylate end group is 3:1, and under a protective atmosphere, adding the second solution into the mixed monomer, and maintaining the mixture in the protective atmosphere until the reaction is completed, to obtain a filling body; The filler is sequentially subjected to column chromatography purification with dichloromethane and spin-dried to obtain a dendritic spiral phenylethylidene copolymer.

8. The method for preparing a dendrite spiral phenylacetylene copolymer according to claim 7, characterized in that: The molar ratio of the branched spiral phenylacetylene monomer to the phenylacetylene monomer with an acrylate end group is 6 to 30:

1.

9. The method for preparing a dendrite spiral phenylethene copolymer according to claim 7, characterized in that: The preparation steps of the branched spiral phenylacetylene monomer are as follows: At room temperature, dissolving a dendritic alkoxy ether monomer having an amino terminal group in the first portion of dry dichloromethane to obtain a third solution; In a protective atmosphere, adding the first portion of N,N-diisopropylethylamine and the first portion of 4-ethynyl pentafluorophenol ester to the third solution, and maintaining the solution in the protective atmosphere until the reaction is complete, to obtain a fourth solution; The fourth solution is sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain the dendrite helical phenylacetylene monomer.

10. The method for preparing a dendrite spiral phenylacetylene copolymer according to claim 7, characterized in that: The preparation steps of the phenylacetylene monomer with an acrylate end group are as follows: Dissolving 2-(2-(2-aminoethoxy)ethoxy)ethanol in a second portion of dry dichloromethane at room temperature to obtain a fifth solution, and dissolving a second portion of 4-ethynyl pentafluorophenol ester in a third portion of dry dichloromethane at room temperature to obtain a sixth solution; Adding a second portion of N,N-diisopropylethylamine to the fifth solution to obtain a seventh solution; The seventh solution is placed in a protective atmosphere, and the sixth solution is slowly added dropwise. After the addition is completed, the solution is kept in the protective atmosphere until the reaction is completed, thereby obtaining an eighth solution; The eighth solution is sequentially subjected to column chromatography purification treatment and spin-dried solvent treatment to obtain an intermediate product; dissolving all of the intermediate product in a fourth portion of dry dichloromethane to obtain a ninth solution; Under a protective atmosphere, adding a second portion of triethylamine to the ninth solution to obtain a tenth solution; Add acryloyl chloride to the fifth portion of dry dichloromethane to obtain an eleventh solution; adding the eleventh solution to the tenth solution until the reaction is complete, and then adding methanol to quench the reaction to obtain a twelfth solution; The twelfth solution is washed with saturated saline. After washing, the lower organic phase is taken out and subjected to spin drying and column chromatography purification in sequence to obtain the phenylacetylene monomer having an acrylate end group.

Citation Information

Patent Citations

  • Phenylacetylene derivative with double chiral carbon atoms on pendant group and preparation method and application thereof

    CN104910046A

  • Spiral polyphenylacetylene derivative with self-assembly characteristic, assembly and preparation method thereof

    CN111825800A

  • Method for inducing polyphenylacetylene self-assembly film formation through light irradiation cross-linking polymerization reaction

    CN115386112A

  • Dendrimer molecular wire, its synthesizing method and fluorescence agent comprising the same

    JP2005255699A